Reduksi Nilai dalam Epistemologi Ilmu Modern: Studi Kritis-Filosofis tentang Islamisasi Ilmu Pengetahuan sebagai Alternatif Epistemik - Maharani Maharani; Salahuddin Harahap (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The epistemology of modern science develops with the assumption that neutrality and objectivity distinguish facts from values. This belief leads to the reduction of values, especially those related to ethical, metaphysical, and spiritual values, during the development of science. The purpose of this paper is to examine the problem of value reduction in the epistemology of modern science and to examine the Islamization of science as an epistemic alternative. This research method is qualitative, literature-based, and critical-philosophical. Epistemological critiques of value-free science, based on positivism and modern empiricism, and a study of the theory of the Islamization of science by Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi are used to complete the analysis. The results of this study indicate that the epistemological separation between facts and values ​​in contemporary science leads to a decline in values. The Islamization of science offers an alternative epistemic framework that positions science as a meaningful, valuable, and goal-oriented activity. Thus, without rejecting the methodological progress of contemporary science, it remains a plausible option. Despite lingering problems with the methodological formulation, this article asserts that the Islamization of science is relevant as a theoretical response to the crisis of values ​​in the epistemology of modern science.